High school students’ motivation for learning English in classes with Native and Non-native English speaking teachers : - Lê, Lưu Tố Quyên (Cantho University, 2019)
The research aims at finding out high school students’ attitudes towards Native and Non-native English speaking teachers and whether students are more motivated in learning English with Native or Non-native English speaking teachers.